Global trends in the research on Legg–Calve–Perthes disease in Web of Science - Qin, Wenbao; He, Mingwei; Qin, Hongsheng; Wei, Qingjun; Yan, Haiwei (Frontiers in Pediatrics, 2024)
Legg-Calve-Perthes disease (LCPD) is a form of idiopathic femoral head necrosis that can lead to permanent femoral head deformities and premature osteoarthritis in children under the age of 15. A bibliometric analysis was performed to investigate the development process and hotspots, as well as the collaboration and influence among countries, institutions, authors, journals, and keywords of papers relevant to LCPD from Web of Science Core Collection (WoSCC) during the period January 1, 2000 to June 30, 2023. In total, there were 2,205 researchers from 916 institutions of 53 countries/regions have participated in 673 papers in 199 academic journals. The research of LCPD has major fluctuation but increasing gradually in the number of articles published over the last two decades. The the USA has the greatest number of publications of LCPD, and the Texas Scottish Rite Hospital for Children was the most productive institution. English was the most widely language used in the world. Herring JA, who both acted as the corresponding and first author, published the most co-cited papers. Journal of Pediatric Orthopaedics published the most numerous of LCPD papers, but the Journal of Bone and Joint Surgery American Volume occupies the highest total citations. The most frequent keywords for publications were about the symptom, mechanism and prognosis, revealing the research focus of most scholars. Our research described the development trends and hotspots in the research field of LCPD and will help researchers make better make decisions.